Pleomorphic adenoma of the hard palate in a 61-year-old patient - Adam Chiżyński; Piotr Osica; Rafał Stelmach; Anna Janas-Naze (Kazimierz Wielki University, 2017)
The article describes a case of pleomorphic adenoma in a 61-year-old patient, its diagnostic methods and treatment.